Numerical investigation on progressive collapse resistance of steel-concrete composite floor systems. Issue 2 (1st February 2021) - Wang, Junjie; Wang, Wei; Bao, Yihai; Lehman, Dawn
Abstract: Steel-concrete composite floor systems are commonly used in steel buildings. Stability under gravity and lateral loading depends on these systems. To better understand the design parameters that govern the progressive collapse behaviour of steel-concrete composite floor systems, high-resolution finite-element analyses (FEA) is conducted. Steel fracture and concrete damage are explicitly considered in the finite-element model (FEM). The model is validated using full-scale test data including comparison of the measured response and failure modes. The validated model is used to conduct a parametric study to investigate untested parameters including (i) concrete strength, (ii) horizontal constraint, (iii) steel deck thickness, (iv) reinforcement ratio in the composite slab, and (v) the number of the shear studs. The simulation results are used to determine the optimum design to increase progressive collapse resistance. Specifically, it is found that increasing the continuity and the horizontal constraint of the steel deck, the steel deck thickness, and number of shear studs increase this resistance. Considering the steel consumption and the common practice in the construction, improving the continuity and the horizontal constraint of the steel deck are the best choices to improve the collapse resistance.